Cyclooxygenase-2 expression and connection with tumor recurrence and histopathologic parameters in gastrointestinal stromal tumors - TÜRKÖZ, HÜSEYİN KEMAL (WILEY-BLACKWELL PUBLISHING, INC, 2009)
Tissue cyclooxygenase-2 (COX-2) is a rate-limiting enzyme in prostaglandin synthesis and has been shown to have roles in carcinogenesis and tumor progression. Evaluation of COX-2 overexpression in malignancies has been performed mostly on tumors of epithelial origin, and little is known about its presence in mesenchymal tumors, especially gastrointestinal stromal tumors (GIST). COX-2 has been reported to be widely expressed in GIST and has been suggested as a potential diagnostic marker. We evaluated the overexpression and roles of COX-2 in tumorigenesis in GIST with regard to its relation to prognostic parameters and tumor recurrence. We studied the presence of COX-2 expression immunohistochemically and its relation to clinicopathologic prognostic variables in 41 cases of GIST. COX-2 was overexpressed in 21 (51%) of 41 tumors. The extent of overexpression was greater in tumors that recurred after surgical resection. COX-2 overexpression was also higher in tumors with coagulative necrosis, high mitotic index and an infiltrative pattern of growth. The observation of greater COX-2 expression levels in GIST with unfavorable histopathologic variables is contrary to previous reports and consistent with the reported roles of COX-2 in carcinogenesis of epithelial malignancies.
Keywords: Cyclooxygenase-2; gastrointestinal stromal tumors; diagnosis; prognosis; immunohistochemistry; CANCER; INHIBITORS; COX-2; ANGIOGENESIS; CARCINOMA; DIAGNOSIS; NEOPLASMS; GISTS; COLON